New genre Arctic art and art education exhibition - Jokela, Timo; fi=Taiteiden tiedekunta|en=Faculty of Art and Design| (fi=Lapin yliopisto|en=University of Lapland|, 2024)
The exhibition is a production of New Genre Arctic Art Education initiative consisting of multiple art-based projects, in which two Thematic Networks of UArctic, Arctic Sustainable Art and Design and Children of the Arctic, combine participatory practices of arts and psychosocial work to develop sustainable art and education. This initiative places the inhabitants of the North and the Arctic, especially the youth, in the center as they will be the creators of the Arctic future.